Are book publications disappearing from scholarly communication in the social sciences and humanities?. Issue 6 (19th November 2018) - Engels, Tim C.E.; Istenič Starčič, Andreja; Kulczycki, Emanuel; Pölönen, Janne; Sivertsen, Gunnar
Abstract : Purpose: The purpose of this paper is to analyze the evolution in terms of shares of scholarly book publications in the social sciences and humanities (SSH) in five European countries, i.e. Flanders (Belgium), Finland, Norway, Poland and Slovenia. In addition to aggregate results for the whole of the social sciences and the humanities, the authors focus on two well-established fields, namely, economics & business and history. Design/methodology/approach: Comprehensive coverage databases of SSH scholarly output have been set up in Flanders (VABB-SHW), Finland (VIRTA), Norway (NSI), Poland (PBN) and Slovenia (COBISS). These systems allow to trace the shares of monographs and book chapters among the total volume of scholarly publications in each of these countries. Findings: As expected, the shares of scholarly monographs and book chapters in the humanities and in the social sciences differ considerably between fields of science and between the five countries studied. In economics & business and in history, the results show similar field-based variations as well as country variations. Most year-to-year and overall variation is rather limited. The data presented illustrate that book publishing is not disappearing from an SSH. Research limitations/implications: The results presented in this paper illustrate that the polish scholarly evaluation system has influenced scholarly publication patterns considerably, while in the other countries the variations are manifested only slightly. The authors conclude that generalizations like "performance-based research funding systems (PRFS) are bad for book publishing" are flawed. Research evaluation systems need to take book publishing fully into account because of the crucial epistemic and social roles it serves in an SSH. Originality/value: The authors present data on monographs and book chapters from five comprehensive coverage databases in Europe and analyze the data in view of the debates regarding the perceived detrimental effects of research evaluation systems on scholarly book publishing. The authors show that there is little reason to suspect a dramatic decline of scholarly book publishing in an SSH.